Presentation. The social forms of the biocitizen - G. Seguel, Andrés; Zabala, Ximena (Universidad Católica del Norte, Instituto de Investigaciones Arqueológicas y Museo, 2019)
This special issue aims to contribute to the discussion around biocitizenship given the transformations in the field of biomedicine in recent years and the increase of social conditions that would be making new forms of citizenship emerge. Effectively for some decades, the forms of social control and the articulation between biology, identity and modern institutions do not follow a stable and univocal path.